A Cross-Cultural Validation of the Learning-Related Boredom Scale (LRBS) With Canadian and Chinese College Students. (February 2013) - Tze, Virginia M. C.; Klassen, Robert M.; Daniels, Lia M.; Li, Johnson C.-H.; Zhang, Xiao
This study evaluated the psychometric properties of the Learning-Related Boredom Scale (LRBS) from the Academic Emotions Questionnaire (AEQ; Pekrun, Goetz, & Perry, 2005; Pekrun, Goetz, Titz, & Perry, 2002) in a sample of 405 university students from Canada and China. Multigroup confirmatory factor analysis was used to test the factor structure and measurement invariance of the LRBS across cultural settings, after which the relationships between the LRBS, boredom frequency in class, intrinsic motivation, and self-efficacy for self-regulated learning (SESRL) were examined. Results showed evidence of reliability and measurement invariance of the LRBS, and the relationships between the LRBS, boredom frequency, and SESRL were similar across settings. The study thus provided evidence that learning-related boredom is a valid construct across culturally diverse school settings and supported the use of the LRBS in both Canadian and Chinese student populations.